Interface shear resistance of clustered shear connectors for precast concrete bridge deck systems. (1st April 2018) - Tawadrous, Raed; Morcous, George
Highlights: Most bridge design codes provide conservative estimates of interface shear resistance of clustered shear connectors. Concrete compressive strength has no significant effect on interface shear resistance for reinforcement ratio less than 4%. Tensile yield strength of shear connectors has no significant effect on interface shear resistance. AASHTO LRFD, fib MC 2010, and EC-2 code provisions provide the most accurate predictions of interface shear resistance. EC-2 and fib MC code provisions provide the most consistent predictions of interface shear resistance. Abstract: Full-depth precast concrete deck systems have been increasingly used in bridge construction due to their high production quality, reduced construction duration, possible weight reduction, and lower life-cycle cost. Precast concrete deck systems are usually made composite with the supporting girders to enhance the structural performance and reduce superstructure depth. Most of the composite systems use clustered shear connectors at large spacing to reduce the number of field-cast connections and simplify production and erection operations. Current prediction models of interface shear resistance were developed for continuous shear connectors in cast-in-place concrete deck systems. This paper investigates the applicability of the existing interface shear prediction models to clustered shear connectors. Sixteen full-scale push-off specimens with clustered shear connectors on concrete and steel girders were tested. Also, the results of 162 push-off experiments obtained from the literature were used to compare the prediction models adopted by AASHTO LRFD, fib MC, Eurocode-2, and CSA-S6 bridge design codes. Comparisons indicated that all design codes provide conservative estimates for interface shear resistance of clustered shear connectors. Parameters affecting the interface shear resistance of clustered shear connectors were also identified.